Specters of war : Hollywood's engagement with military conflict - Bronfen, Elisabeth (Rutgers University Press, 2012)
Specters of War: Hollywood's Engagement with Military Conflict looks at the way war has been brought to the screen in various genres and at different historical moments throughout the twentieth century. Elisabeth Bronfen asserts that Hollywood has emerged as a place where national narratives are created and circulated so that audiences can engage with fantasies, ideologies, and anxieties that take hold at a given time, only to change with the political climate.